Efektywność współpracy naukowo-biznesowej na tle pandemii COVID-19 w Polsce = Effectiveness of scientific and business cooperation against the background of the COVID-19 pandemic in Poland - Gębska, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The COVID-19 pandemic in 2019-2021 became a challenge for the economies of all countries due to solutions that were supposed to prevent the disease from transmitting between people. One of the tools proposed by administrative units and medical services was a lockdown and stagnation of the entire economy. The sector that particularly needed scientific and business support was the one related to the protection of human health and life. The result of such cooperation is the speed at which vaccines for the SARS-CoV-2 disease caused by the coronavirus were developed.
Keywords: pandemia; współpraca; nauka-biznes; zarządzanie; cooperation; pandemic; science-business; management